PersepsiMasyarakat Terhadap Kinerja Dokter - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
The Community Perception on Physician Performance The educational curriculum that have provided by school of medicine could influence a graduated performance. The community perception of physician performance can be used as indirect an instruments to assess the medical educational curriculum. The survey research about physician performance has been provided in Yogyakarta province. The fifth aspect of physician performance such as: professionalism, health services ability, patient management, collaboration, and efficiency and effectiveness have been taken in this survey. Survey is provided through "close questions or statements", respond each of an item of statement is chosen between strongly disagree to strongly agree or between 0 tol 0. Maximal value of performance is presented and that be given mark 10 as ideal performance value. The means of mark in this item of each aspect is used as result of performance. Research result presented that the fifth aspect of physician performance still far from community desiring. Some weakness of physician performance that protruding has been founded, that is: perception of advice and critic, feedback receipting, personal communication and collaboration ability, patient management, and documentation medical record.